Characterization, diversity, and biogeochemical potential of soil viruses inhabiting in Yuncheng Salt Lake - Liu, Jin; Dong, Xiaoxiao; Wang, Xiaokai; Chu, Yunmeng (Frontiers in Microbiology, 2025)
Viruses play a crucial role in microbial communities and can significantly influence ecosystem processes and biogeochemical cycles by regulating the structure of these communities and the metabolic functions of their hosts. Salt lakes are recognized for harboring a diverse array of halotolerant microorganisms; however, there is limited knowledge regarding the viruses and their co-occurring hosts in these halotolerant environments. Herein, 3,362 viral operational taxonomic units (vOTUs) were recovered from Yuncheng Salt Lake soils by combining with a binning method, with less than 2% showing homology to known viruses, highlighting a significant unexplored viral diversity. Virus communities were typically specific to their habitats, exhibiting low overlap across various geographical regions and other ecological environments. It was predicted that 27.4% of viruses were associated with microbial host populations, and the majority of the predicted vOTUs are linked to dominant bacteria and archaea. Metabolic predictions revealed that 568 putative auxiliary metabolic genes (AMGs) were involved in various processes related to biosynthesis and transformation reactions associated with resource utilization within host cells. The virus-encoded AMGs indicated that these viruses influenced the metabolism of carbon, nitrogen, sulfur, and phosphorus in microorganisms, as well as their adaptation to salinity. This study highlighted the unique characteristics and potential ecological roles of soil viruses in Yuncheng Salt Lake, suggesting that these viruses may significantly influence microbial communities and the biogeochemistry of salt lake soils. These findings provide valuable insights into the diversity, function, and ecology of viruses in soils surrounding salt lakes, establishing a foundation for understanding their roles in these unique ecosystems.